PHYSIOCHEMICAL, IN-VITRO, EX-VIVO AND IN-VIVO EVALUATION OF TRANSDERMAL PATCHES BASED ON QBD APPROACH: AN OVERVIEW - DUBEY, RUPAL; POTHUVAN, UMADOSS; PANDEY, ARUN KUMAR; GUPTA, BHASKAR KUMER (International Journal of Applied Pharmaceutics, 2022)
There are various forms of prescription drugs available in the market for human and animal purposes, which may be administered for acute or chronic treatment. And a variety of dosage regimens of different dosage forms are found in general, among which one of the treatment modes is the transdermal route. The Transdermal Tract Route is a more accurate way to get into the skin without pain, faster to systemic circulation than the oral route and the drug reaches the systemic circulation in a controlled transmission. Improving the transdermal system poses an additional challenge to maintain Quality by Design (QbD) with quality, consistency, reproduction, stability and efficiency. With the QbD method of pharmaceutical product production, product quality is considered much faster than waiting until the end to be tested for quality. In essence, this includes determining the sources of the unpredictability that may be contributing to the process. This approach ensures that the causes of quality problems are identified. The main result is a pharmaceutical product manufactured to meet pre-determined quality requirements from the outset. In essence, this includes determining the sources of the unpredictability that may be contributing to the process. This approach ensures that the causes of quality problems are identified. The main result is a pharmaceutical product manufactured to meet pre-determined quality requirements from the outset. Critical quality attribute (CQA) and Critical Process Parameters can be used to establish QbD (CPP). During the construction of a transdermal design, it is important to check the various key parameters that help maintain the Quality Target Product Profile (QTPP) of the drug product.